Study of the Effect of Adapter Design on the Load Distribution in the Bearing Units of Freight Cars - I.E, Martynov; A .V, Trufanova; V.M, Petukhov; V.M, Ischenco; N.S, Kladko (International Journal of Engineering and Technology, 2018)
The possibility of increasing the service life of 18-100 three-piece bogies by using taper bearing units with different types of adapters is considered in the article. The main task is the need to increase the longevity of the running parts of freight cars by reducing their dynamic loading. The solution of this problem is possible by improving the axle boxes. To determine possible design solutions, an analysis was made of modern domestic and foreign designs of bogies using bearing assemblies with adapters and three types of adapters with the highest quality indicators, namely the half-box of the 18-7020 bogie, adapter with elastic packing and adapter of the 18-4129 bogie. Three models of adapters were investigated using the finite-elements method, which, in accordance with reported manufacturerâ€™s data, have high reliability index and can provide equal load distribution between bearing systems rollers. The results of mathematical simulation suggest that the forces applied to the bearing systems rollers largely depend on the adapter design. Furthermore, the studied adapter designs are not acceptable and require further designing.Â Â